2014
DOI: 10.1164/rccm.201406-1095oc
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells Induce Necroptosis of Lung Endothelial Cells and Increase Susceptibility to Lung Inflammation

Abstract: Rationale: Red blood cell (RBC) transfusions are associated with increased risk of acute respiratory distress syndrome (ARDS) in the critically ill, yet the mechanisms for enhanced susceptibility to ARDS conferred by RBC transfusions remain unknown.Objectives: To determine the mechanisms of lung endothelial cell (EC) High Mobility Group Box 1 (HMGB1) release following exposure to RBCs and to determine whether RBC transfusion increases susceptibility to lung inflammation in vivo through release of the danger si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 52 publications
8
94
0
Order By: Relevance
“…In the current study, only plasma RIP3 levels at 48 hours, rather than on presentation, were associated with RBC transfusions, consistent with the hypothesis that transfusion augments necroptotic pathway activation and RIP3 release in humans. This relationship is mechanistically plausible: we have previously shown that RBC transfusion can cause necroptosis in endothelial cells, and that plasma RIP3 increases significantly in mice after RBC transfusion (18). Larger studies may further elucidate the potential contribution of necroptosis to mechanisms underlying the association of RBC transfusion with AKI.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the current study, only plasma RIP3 levels at 48 hours, rather than on presentation, were associated with RBC transfusions, consistent with the hypothesis that transfusion augments necroptotic pathway activation and RIP3 release in humans. This relationship is mechanistically plausible: we have previously shown that RBC transfusion can cause necroptosis in endothelial cells, and that plasma RIP3 increases significantly in mice after RBC transfusion (18). Larger studies may further elucidate the potential contribution of necroptosis to mechanisms underlying the association of RBC transfusion with AKI.…”
Section: Discussionmentioning
confidence: 89%
“…We used a commercially available enzyme-linked immunosorbent assay (CUSABIO, Wuhan, China) to measure plasma RIP3 as previously described (18). Performing personnel were blind to each subject's AKI status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In culture, Qing and colleagues showed that lung endothelial cells undergo necrotic cell death with prolonged RBC exposure. 22 In cardiac surgery, packed RBC transfusions have been linked to pulmonary dysfunction and decreased survival. 23,24 Lungs appear to be susceptible to packed RBC-induced injury in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK3 is not specific to the heart, so other reasons besides myocardial infarction for elevated levels of RIPK3 on Day 1 cannot be ruled out. Only a few studies of human pathology have examined levels of RIPK3 expression and their association with clinical outcomes (26,27). The current results suggest that the serum level of RIPK3 increased significantly 24 hours after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 53%